Study of Distribution Transformer Voltage Drops in Feeder 5 Out Going Districts 4 and 6 at PT. PLN (Persero) Tarakan City, North Kalimantan - Arifin, Marthen; Mado, Ismit; Budiman, Achmad; Anwar, Choirul; Nathanael, Samuel (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
This research aims to determine the low-voltage drop that occurs at the substation and on the customer side. The voltage drop is affected by many factors, including line resistance, line current, power factor, and line length. The need for electric power is increasing every year, causing power losses and voltage drops in the network to be a major concern. This research was conducted at Feeder 5, outgoing villages 4 and 6, one of the areas of PT. PLN in Tarakan City. The research data is voltage measurement data. This research applies analytical calculations with a quantitative descriptive method compared to calculations based on ETAP software. The allowable voltage drop by SPLN is 5% of the nominal voltage. The results of the analysis show that the average voltage drop that occurs is still within the limits permitted by the SPLN, namely below 5% of the nominal voltage.